2023
DOI: 10.1088/1402-4896/ace79c
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Brink-Axel Hypothesis for calculations of allowed stellar weak rates of heavy nuclei

Abstract: The knowledge of beta-decay transitional probabilities and Gamow-Teller (GT) strength functions from highly excited states of nuclides is of particular importance for applications to astrophysical network calculations of nucleosynthesis in explosive stellar events. These quantities are challenging to achieve from the experimental measurements or computations using various nuclear models. Due to unavailability of feasible alternatives, many theoretical studies often rely on the Brink-Axel (BA) hypothesis, that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…The majority of the previously calculated set of weak rate calculations [24,[30][31][32][33] used an approximate method invoking the socalled Brink-Axel (BA) hypothesis [34,35]. Several studies have investigated the accuracy of the BA hypothesis [36][37][38][39][40][41][42][43][44][45][46][47]. Most of these works have shown that the BA hypothesis is a poor approximation for usage in calculations related to stellar weak rates.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the previously calculated set of weak rate calculations [24,[30][31][32][33] used an approximate method invoking the socalled Brink-Axel (BA) hypothesis [34,35]. Several studies have investigated the accuracy of the BA hypothesis [36][37][38][39][40][41][42][43][44][45][46][47]. Most of these works have shown that the BA hypothesis is a poor approximation for usage in calculations related to stellar weak rates.…”
Section: Introductionmentioning
confidence: 99%